Compressive Interferenceless Coded Aperture Correlation Holography With High Imaging Quality - Liu, Chao; Man, Tianlong; Wan, Yuhong (Frontiers in Photonics, 2022)
Interferenceless coded aperture correlation holography (I-COACH) provides an alternative way for the 3D imaging of spatial incoherent illuminated or fluorescent sample. However, the low imaging signal-to-noise ratio is one of the bottlenecks that restrict the application of I-COACH. The limitation is mainly originated from the strong bias level that presents in the recorded holograms. Phase shifting methods were implemented in I-COACH to eliminate the background noise while the multiple-exposures recording mechanism reduces significantly the temporal resolution of the system. In this paper, we proposed a compressive I-COACH imaging method with high reconstruction quality and without the sacrifice of the imaging speed. The 3D holographic image reconstruction was implemented under compressive sensing framework while only one single-exposure object hologram and one point spread hologram are necessary. High quality reconstructions were obtained using the proposed method, even for the down-sampled holograms. The imaging signal-to-noise ratio (SNR) of the I-COACH system was improved by a factor of more than 16.5% when comparing with the imaging SNR obtained by conventional cross-correlation reconstruction method. The proposed method provides a fast and high-fidelity imaging method that can potentially benefit the imaging through scattering medium, partial aperture imaging, and other fields.